Negative Weights are No Concern in Design-Based Specifications - Borusyak, Kirill,Hull, Peter (National Bureau of Economic Research, 2024)
Recent work shows that popular partially-linear regression specifications can put negative weights on some treatment effects, potentially producing incorrectly-signed estimands. We counter by showing that negative weights are no problem in design-based specifications, in which low-dimensional controls span the conditional expectation of the treatment. Specifically, the estimands of such specifications are convex averages of causal effects with
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Kausalanalyse; Schätztheorie; Cross-Sectional Models; Spatial Models; Treatment Effect Models; Quantile Regressions; Instrumental Variables (IV) Estimation